1994
DOI: 10.1021/ma00089a009
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric Mesophases Formed by the Modified Biological Macromolecule 3,6-O-(Butyl Carbamate)-N-phthaloyl Chitosan

Abstract: Cholesteric liquid crystalline phases were observed in dimethyl sulfoxide solutions of a new chitosan derivative. This chitosan derivative had a substitution pattern which approximates that of 3,6-0-(butyl carbamate)-N-phthaloyl chitosan (BuCaPhCh). UV-visible and circular dichroic (CD) spectroscopy carried out on BuCaPhCh revealed that the cholesteric pitch is in the visible wavelength (X) region and is left-handed for all investigated polymer weight fraction, x, values (0.50, 0.56, 0.60, and 0.70) and soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…In Fig. 11 45. A similar inversion of the helical twist has been observed for a lyotropic series of CTC in a mixture of diethylene glycol monoethyl ether (DEME) and 2-pentanone [8,44].…”
Section: Cpc-core Mesomorphic Systemssupporting
confidence: 66%
See 1 more Smart Citation
“…In Fig. 11 45. A similar inversion of the helical twist has been observed for a lyotropic series of CTC in a mixture of diethylene glycol monoethyl ether (DEME) and 2-pentanone [8,44].…”
Section: Cpc-core Mesomorphic Systemssupporting
confidence: 66%
“…Chitin consists of 2-acetamido-2-deoxy-β-D-glucose units linked together through a β(1!4) linkage, and chitosan is an N-deacetylated derivative of chitin. In contrast to the situation for cellulose derivatives, there have been only a limited number of studies of the liquid crystalline behavior of chitin or chitosan derivatives [45][46][47][48][49], except for the mesophase characterization of chitin nanocrystals (microfibrils) [3,50]. The authors' group synthesized chitosan phenylcarbamate (CtsPC) samples of varying DS (2.7-3.7) and examined the liquid crystalline characteristics in polar aprotic solvents [49].…”
Section: Cpc-core Mesomorphic Systemsmentioning
confidence: 99%
“…Rout and coworkers [8][9][10] reported that N-phthalolyl chitosan, N-phthalolyl-3,6-di-O-acetyl chitosan, and N-phthalolyl-3,6-O-(butyl carbamate) chitosan had a lyotropic liquid-crystal property in dimethyl sulfoxide. The critical concentrations (C*'s; i.e., the lowest concentrations to form lyotropic liquid crystals) of these polymers were 0.25-0.27, 0.1, and 0.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 Rout and colleagues found cholesteric solutions in N-phthalolyl chitosan and N-phthaloyl-3,6-di-Oacetyl chitosan dissolved in organic solvents. [7][8][9] Ratto et al investigated the mesophase of water/ chitosan systems with differential scanning calorimetry. 10 Dong and colleagues demonstrated the lyotropic liquid crystallinity of some chitosan derivatives and studied structure factors such as molar mass and degree of substitution on critical concentration (C*) forming the liquid-crystal phase.…”
Section: Introductionmentioning
confidence: 99%